Evaluation Of The Total Quality Management (Tqm) Of Iraqi Insurance Companies According To The Philosophy Of Intelligent Management - Abdul – Kareem, Faaizah (Opción, 2019)
Purpose This research aims at presenting the view based on the assessment of TQM in the Iraqi insurance companies and its application to quality principles, and exploring the requirements of the philosophy of smart management and its impact on TQM. study aims : This study aims to identify the philosophy of smart management of organizations and their impact on total quality management, and on the other hand to identify the extent to which the principles of TQM in the Iraqi insurance companies. Design/methodology/approach: The methodology was used to collect data in order to develop a reliable and correct measurement model for the research variables. The hypotheses were tested through the use of some statistical treatments. A sample of 38 managers and heads of departments of Iraqi insurance companies was used. Practical implications This study provides a useful measure of the relationship between TQM and intelligent management. Original- ity / value - This study is undertaken with the help of senior management in the insurance sector to address the challenge of applying TQM requirements and smart management principles to improve the performance of insurance companies.